Self-Compassion, Frustration Intolerance and OCD Symptoms among Spouse of OCD Patients - Yousaf, Nimra; Majeed, Ayesha (Pakistan Journal of Applied Psychology (PJAP), 2022)
The present research was conducted to investigate the relationship among self-compassion, frustration intolerance and obsessive compulsive disorder symptoms in spouses of OCD patients. Purposive sampling technique was used and sample comprised of 80 participants with the distribution of 40 males and 40 female spouses of OCD patients. The age range of spouses of OCD patients was 20 to 40 years (M=1.50, SD= .50). Self-compassion scaleshort form (Raes, Pommier, Neff & Van Gucht, 2011), frustration discomfort scale (Harrington, 2005) and obsessive compulsive inventory-revised (Foa, 2002) were administered on the participants. The findings of the current study uncovered that self-compassion had a significant negative relationship with frustration intolerance (r= -.80**, p<.01) and with obsessive compulsive disorder symptoms (r=-.77**, p<.01). Findings also revealed that frustration intolerance had a significant positive relationship with obsessive compulsive disorder symptoms (r=.98**, p<.01). Multiple regression analysis signified that self-compassion and frustration intolerance both found to be significant predictors of obsessive compulsive symptoms among spouses of obsessive compulsive disorder patients. Male spouse scored higher on self-compassion while scored lower on frustration intolerance and obsessive compulsive symptoms as compared to female spouse.